Reading and learning to read - Vacca, Jo Anne L. (Boston Pearson, 2009)
Promotes a comprehensive approach to teaching reading and writing with an emphasis on research-based best practices, integrating technology, and accommodating the needs of diverse and struggling learners.--from publisher description.
1. Knowledge and beliefs about reading -- 2. Approaches to reading instruction -- 3. Meeting the literacy needs of diverse learners -- 4. Early literacy: from birth to school -- 5. Inviting beginners into the literacy club -- 6. Assessing reading performance -- 7. Word identification -- 8. Reading fluency -- 9. Vocabulary knowledge and concept development -- 10. Reading comprehension -- 11. Reading-writing connections -- 12. Bringing children and literature together -- 13. Basal readers and instructional materials -- 14. Making the transition to content area texts -- 15. Managing and organizing an effective classroom -- Appendix A. Beliefs about reading interview -- Appendix B. The DeFord Theoretical Orientation to Reading Profile (TORP) -- Appendix C. Reading and writing accomplishments of young children by grade level -- Appendix D. Trade books that repeat phonic elements -- Appendix E. Annotated bibliography of read-aloud books for developing phonemic awareness -- Appendix F. Recommended books for multicultural reading experiences -- Appendix G. International Reading Association standards for reading professionals
Keywords: Reading (Elementary); Language arts (Elementary)